2018
DOI: 10.1007/s13346-018-00608-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a thermostable microneedle patch for polio vaccination

Abstract: The aim of this study was to develop a dissolving microneedle (MN) patch for administration of inactivated polio vaccine (IPV) with improved thermal stability when compared with conventional liquid IPV. Excipient screening showed that a combination of maltodextrin and D-sorbitol in histidine buffer best preserved IPV activity during MN patch fabrication and storage. As determined by D-antigen ELISA, all three IPV serotypes maintained > 70% activity after 2 months and > 50% activity after 1-year storage at 5 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 51 publications
0
39
0
1
Order By: Relevance
“…A recent review by Nguyen and Park summarizes human studies with MNs and reports the progress toward appropriate use of MN arrays in the clinical setting. [34] A suitable formulation of the MN patches exhibited superior thermostability that could enable the mass distribution of IPV vaccines with less dependence on cold chain storage. Zhang et al showed that when MNs were used to deliver DNA vaccines, the gene expression and corresponding immune responses were greatly improved compared to the results of conventional needle injection.…”
Section: Therapeutics and Beyondmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent review by Nguyen and Park summarizes human studies with MNs and reports the progress toward appropriate use of MN arrays in the clinical setting. [34] A suitable formulation of the MN patches exhibited superior thermostability that could enable the mass distribution of IPV vaccines with less dependence on cold chain storage. Zhang et al showed that when MNs were used to deliver DNA vaccines, the gene expression and corresponding immune responses were greatly improved compared to the results of conventional needle injection.…”
Section: Therapeutics and Beyondmentioning
confidence: 99%
“…The group of Prausnitz, the pioneer of the MN-based device, developed a dissolving MN patch for the administration of the inactivated polio vaccine (IPV) with greater thermal stability than that of the conventional liquid IPV. [34] A suitable formulation of the MN patches exhibited superior thermostability that could enable the mass distribution of IPV vaccines with less dependence on cold chain storage. Because global vaccination strategies require increased immunization coverage and reduced costs, a new dissolving MN array has been proposed by Courtenay et al as an alternative approach to the hypodermic needle, offering the prospect of selfvaccination.…”
Section: Therapeutics and Beyondmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies on vaccines suggest that vaccines administered in solid dosage forms have a potential advantage over liquid dosage forms, as they provide a higher level of immunogenicity, thus leading to a dose-sparing effect [3]. Solid dosage forms also have many other advantages over liquid dosage forms in terms of avoiding the need for cold chain storage, less training for vaccinators and a lower cost [4,5]. If these solid dosage forms can be made needle-free this will also minimise the chance of disease transmission from needle-stick injury and increase patient compliance, as it would be pain-free.…”
Section: Introductionmentioning
confidence: 99%